Peningkatan Kualitas Pelayanan dengan Metode Quality Function Deployment (QFD) pada Koperasi di Cv. Zai Berkat Mandiri - Bastuti, Sofian; Alfatiyah, Rini; Zega, Pasti Niatan (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2024)
CV. Zai Berkat Mandiri Cooperative is an economic entity actively supporting the community in economic matters and achieving social prosperity. This study aims to evaluate the enhancement of service standards through the application of Quality Function Deployment (QFD) techniques at CV. Zai Berkat Mandiri Cooperative. The QFD method is used to identify the actual needs of customers and link them with the cooperative's internal processes. This research involves the analysis of primary data by distributing a preliminary questionnaire (pretest) to 85 respondents. The study results indicate high needs but low customer satisfaction in factors such as the comfort of the waiting area (65%), the layout and tidiness of the waiting area and the arrangement of places used by customers (69%), services to customers based on the received queue number (68%), parking area security (65%), and the attentiveness of customer service (66%). There is a gap between customer expectations and the services provided. The cooperative is advised to improve service quality by enhancing the comfort of the waiting area, parking area security, and customer service attentiveness. The findings of this study are expected to assist other cooperatives in strengthening their position in a competitive market through internal process changes, employee training, and improvement of other facilities.